Admissions processes for five year medical courses at English schools: review. Issue 7548 (16th March 2006) - Parry, Jayne; Mathers, Jonathan; Stevens, Andrew; Parsons, Amanda; Lilford, Richard; Spurgeon, Peter; Thomas, Hywel
Abstract: Objective To describe the current methods used by English medical schools to identify prospective medical students for admission to the five year degree course. Design Review study including documentary analysis and interviews with admissions tutors. Setting All schools (n = 22) participating in the national expansion of medical schools programme in England. Results Though there is some commonality across schools with regard to the criteria used to select future students (academic ability coupled with a "well rounded" personality demonstrated by motivation for medicine, extracurricular interests, and experience of team working and leadership skills) the processes used vary substantially. Some schools do not interview; some shortlist for interview only on predicted academic performance while those that shortlist on a wider range of non-academic criteria use various techniques and tools to do so. Some schools use information presented in the candidate's personal statement and referee's report while others ignore this because of concerns over bias. A few schools seek additional information from supplementary questionnaires filled in by the candidates. Once students are shortlisted, interviews vary in terms of length, panel composition, structure, content, and scoring methods. Conclusion The stated criteria for admission to medical school show commonality. Universities differ greatly, however, in how they apply these criteria and in the methods used to select students. Different approaches to admissions should be developed and tested.